2013
DOI: 10.1371/journal.pone.0059056
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis Using Exon Arrays Demonstrates an Important Role for Expression of Extra-Cellular Matrix, Fibrotic Control and Tissue Remodelling Genes in Dupuytren's Disease

Abstract: Dupuytren's disease (DD) is a classic example of pathological fibrosis which results in a debilitating disorder affecting a large sector of the human population. It is characterized by excessive local proliferation of fibroblasts and over-production of collagen and other components of extracellular matrix (ECM) in the palmar fascia. The fibrosis progressively results in contracture of elements between the palmar fascia and skin causing flexion deformity or clawing of the fingers and a severe reduction in hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 68 publications
(124 reference statements)
1
21
0
Order By: Relevance
“…Type I collagenolysis is mediated by secreted, as well as membrane-anchored members of the matrix metalloproteinase (MMP) gene family during fibroblast-mediated matrix remodeling [22]. MMP16 is part of the matrix metalloproteinase (MMP) gene family that is directly relevant to fibrosis [23]. Previous reports demonstrated that severe hypoxia existed in regressive scars, and oxygen levels return to normal in mature scars, findings that are consistent with dynamic changes in microvessel density [5].…”
Section: Discussionmentioning
confidence: 99%
“…Type I collagenolysis is mediated by secreted, as well as membrane-anchored members of the matrix metalloproteinase (MMP) gene family during fibroblast-mediated matrix remodeling [22]. MMP16 is part of the matrix metalloproteinase (MMP) gene family that is directly relevant to fibrosis [23]. Previous reports demonstrated that severe hypoxia existed in regressive scars, and oxygen levels return to normal in mature scars, findings that are consistent with dynamic changes in microvessel density [5].…”
Section: Discussionmentioning
confidence: 99%
“…Type I collagenolysis is mediated by secreted, as well as membrane‐anchored members of the matrix metalloproteinase (MMP) gene family during fibroblast‐mediated matrix remodeling [Sabeh et al, ]. MMP16 is part of the matrix metalloproteinase (MMP) gene family that is directly relevant to fibrosis [Forrester et al, ].…”
Section: Pathophysiology Of Hsmentioning
confidence: 99%
“…Further proteins are platelet-derived growth factor (PDGF), fibroblast growth factor (FGF), epidermal growth factor (EGF) and interleukin-1 (IL-1), as well as the cell matrix proteins Tenascin and Periostin that also affect differentiation, growth and contractility of myofibroblasts. However, the exact pathogenesis and pathology have yet to be decrypted [1,[9][10][11][12].…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%